1975
DOI: 10.1063/1.430359
|View full text |Cite
|
Sign up to set email alerts
|

High resolution study of photoionization processes in O2

Abstract: Relative photoionization efficiency curves were determined for the production of O+2, O+, and O− from molecular oxygen in the wavelength region of the helium continuum. The photoionization efficiency curve for O+2, determined at a wavelength resolution (FWHM) of 0.07 Å throughout most of the region from 1030–580 Å, shows rotationless autoionization structure which is broadened due to the processes of predissociation and/or autoionization. The photoionization effciency curves for fragment ions from ion pair for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(91 citation statements)
references
References 23 publications
4
87
0
Order By: Relevance
“…For O-, anyone of the measured four ratios, both at 488.0nm and at 514.5nm, consistently yields f<0.1. For S , the energy dependence of the partial cross sections [3,10,24] cannot be ignored across the photoelectron spectrum as a result of larger fine-structure splittings and closer location to threshold (the electron affinity of S is 2.077 eV [3-1, that of O is 1.462 eV [2,16]). As for O-, the d-wave contribution is small for S-, and the measured branching ratios suggest f<0.1.…”
Section: I(i--* M)/i(i ~ N) = (G~" + Ug~")/(g~" + Fg~")mentioning
confidence: 99%
“…For O-, anyone of the measured four ratios, both at 488.0nm and at 514.5nm, consistently yields f<0.1. For S , the energy dependence of the partial cross sections [3,10,24] cannot be ignored across the photoelectron spectrum as a result of larger fine-structure splittings and closer location to threshold (the electron affinity of S is 2.077 eV [3-1, that of O is 1.462 eV [2,16]). As for O-, the d-wave contribution is small for S-, and the measured branching ratios suggest f<0.1.…”
Section: I(i--* M)/i(i ~ N) = (G~" + Ug~")/(g~" + Fg~")mentioning
confidence: 99%
“…This implies the existence of different mechanisms for producing these alternative sets of final states. This situation is clarified by two facts : At 584 A only the first four or five vibrational levels are populated by direct photoionization, whereas I = 736 A hits an autoionizing line in the photoabsorption spectrum [64] of 0,. This suggests that the lower levels are produced by direct photoionization, and the upper levels by the indirect process.…”
Section: Indirect Processesmentioning
confidence: 99%
“…Neutral excited states lying at 10-50 eV often interact with ion-pair continua and their predissociation produces a pair of negative ion and positive ion, and, in some cases, additional neutral fragment(s). Several authors including our group have shown that the detection of the negative ions thus produced is a sensitive probe to study the properties of superexcited states [9][10][11][12][13], because the configuration coupling between neutral and ion-pair states depends on the shape of the potential-energy surfaces and the symmetry of the excited state orbital.…”
Section: Introductionmentioning
confidence: 99%